SPEECH DEVELOPMENT OF CHILDREN WITH HEARING IMPAIRMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the speech development of children with hearing impairments, highlighting the unique challenges they face in acquiring spoken language. It discusses the impact of varying degrees of hearing loss on speech development, the importance of early intervention, and effective strategies for fostering language skills. The article aims to provide insights for educators, parents, and clinicians to support the speech development of children with hearing impairments.